2018
DOI: 10.1016/j.tcb.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Senescence-Focused Cancer Therapies

Abstract: Damaged cells at risk of neoplastic transformation can be neutralized by apoptosis or engagement of the senescence program, which induces permanent cell-cycle arrest and a bioactive secretome that is implicated in tumor immunosurveillance. While from an evolutionary perspective senescence is beneficial in that it protects against malignancies, the accumulation of senescent cells in tissues and organs with aging and at sites of various pathologies is largely detrimental. Because induction of senescence in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 123 publications
(197 reference statements)
5
164
0
Order By: Relevance
“…[101][102][103] The idea of ameliorate aged tissue functionality by killing senescent cells is supported by different studies. [104][105][106] Anticancer prosenescence therapies are currently under investigation, 27,107,108 and recently approved drugs, such as CDK4/6 selective inhibitors, have been shown to induce tumor senescence. 25,26,109 Senescence induction in cancer cells may represent a valid approach to restrain tumor growth, but persistent senescent tumor cells may act as the silent factor for tumor relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[101][102][103] The idea of ameliorate aged tissue functionality by killing senescent cells is supported by different studies. [104][105][106] Anticancer prosenescence therapies are currently under investigation, 27,107,108 and recently approved drugs, such as CDK4/6 selective inhibitors, have been shown to induce tumor senescence. 25,26,109 Senescence induction in cancer cells may represent a valid approach to restrain tumor growth, but persistent senescent tumor cells may act as the silent factor for tumor relapse.…”
Section: Discussionmentioning
confidence: 99%
“…“Acute” senescence, when senescent cells are promptly removed from organs, contributes to tissue repair, while “chronic” senescence, due to the persistence of senescent cells in tissues, promotes tissue ageing and inflammation, thus, enhancing tumorigenesis. This double aspect of senescence has arisen much interest in uncovering the faith of senescent cells in tissues, especially in cancer settings, as it has become clear that the efficacy of certain chemotherapeutic drugs relies on the induction of senescence and prosenescence therapy is approaching . So, targeting senescent cells is now a major issue of the scientific community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work, largely in the field of aging, but also in cancer, has identified senolytic agents, drugs whose cytotoxicity has a high degree of specificity against senescent cells. Among these are drugs such as navitoclax that suppress antiapoptotic proteins, Hsp90 inhibitors, and histone deacetylase inhibitors (10). It is suggested that these drugs could be used as "clearing" agents to eliminate residual senescent tumor cells surviving after chemotherapy or radiation, with the goal of delaying or ideally preventing disease recurrence.…”
Section: Strategies To Eliminate Senescent Tumor Cells In Efforts To mentioning
confidence: 99%
“…4, B to D). TP53 is known to suppress the NF-kB/SASP response (33,34), and this effect is emerging as a relevant component of TP53-dependent tumor suppression given that accumulation of SASP-expressing cells is an established driver of tumorigenesis (35). We independently validated the corresponding alterations in NF-kB protein expression, demonstrating that the NFKB1 (p50) and NFKB2 (p52) subunits were expressed at lower levels in BRCA2 carrier tissues compared to controls ( Fig.…”
Section: Brca2 Mut/+ Lp Cells Show Increased Tp53 Activity and Decreamentioning
confidence: 91%